2015
DOI: 10.18805/lr.v0iof.6849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron source on iron deficiency induced chlorosis in groundnut

Abstract: In a field study, the effect of iron source through foliar as well as basal application was studied on lime induced iron-deficiency chlorosis (LIIC), chlorophyll content, nitrate reductase activity, available Fe and micronutrients in groundnut.The visual chlorotic rating screen of various Fe-efficient and Fe-inefficient cultivars clearly identified Fe-efficient and Fe-inefficient. Tirupati-4 was showing symptoms of chlorosis and was Fe-inefficient. Fe absorption capacity varied among cultivars. Applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Pattanashetti et al [43] also observed enormous genetic variation in SCMR reading of groundnut mini core collection across five growth stages. Similar results were also reported by Mann et al [44] and Song et al [45], where lower SPAD values were recorded in no Fe received plants (-Fe) as compared to the plants treated with iron. This might be due to the association of iron in the biosynthesis of the porphyrin ring of chlorophyll.…”
Section: Spad Chlorophyll Meter Readingsupporting
confidence: 90%
“…Pattanashetti et al [43] also observed enormous genetic variation in SCMR reading of groundnut mini core collection across five growth stages. Similar results were also reported by Mann et al [44] and Song et al [45], where lower SPAD values were recorded in no Fe received plants (-Fe) as compared to the plants treated with iron. This might be due to the association of iron in the biosynthesis of the porphyrin ring of chlorophyll.…”
Section: Spad Chlorophyll Meter Readingsupporting
confidence: 90%
“…In present experiment, the response of these two genotypes to various foliar applications was studied. Foliar application of Fe is a common mean to correct Fe deficiency in agricultural crops (Mann et al 2017;Álvarez-Fernández et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Foliar applications of various chemicals are useful in combating Fe deficiency. Foliar applications of FeSO 4 can increase leaf Fe concentration, while basal treatments are more effective for long results (Mann et al, 2017). Under 21 days of Fe deficiency treatment, foliar applications of salicylic acid and sodium nitroprusside in combination increased the level of chlorophyll, active Fe and increased Fe accumulation was observed in cell organelles showing less symptoms of interveinal chlorosis (Kong et al 2014) Different foliar applications containing (FeSO 4 .7H 2 O, Fe(III)-citrate, Fe(III)-EDTA, Fe(III)-DTPA, Fe(III)-IDHA) and a surfactant were able to correct Fe deficiency in Prunus persica L. Foliar applications always resulted in leaf chlorophyll increase, although different degrees of re-greening were observed for the various Fecompounds tested.…”
Section: Introductionmentioning
confidence: 99%
“…Calcareous soils cover major cultivated land of south Mediterranean lands, which decreased crop growth and yield under low Fe availability. A lot of research showed that the most obvious effect of Fe deficiency is a decrease in the amount of chlorophyll pigments [ 7 , 8 ]. Therefore, there is a close relationship between plant growth and photosynthesis [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a close relationship between plant growth and photosynthesis [ 7 , 9 ]. In fact, Mann [ 8 ] and Ren [ 9 ] showed that plants responded strongly to iron deficiency in physiological traits where chlorophyll content and plant biomass were reduced [ 10 ]. Hence, in calcareous soils, cultivating Fe-efficient plants is important for maintaining yields while enhancing environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%